Spontaneous use of Generative Artificial Intelligence and influence on collaborative learner writing - Kossi Seto Yibokou; Alex Boulton; Carmenne Kalyaniwala; Marc Schires (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
The field of education and language learning has been fundamentally impacted by Generative Artificial Intelligence (GenAI) and especially ChatGPT in the last two years. This study examines AI in language teaching and learning, and investigates the influence of GenAI on learners’ collaborative writing in English as an additional language (Lx). A dataset of 190 written assignments by groups of participants enrolled in a third-year undergraduate degree in France was extracted and analysed with tools including Python, Excel and AntConc. Findings reveal 40% of the groups openly declaring use of AI for their written assignments, though subsequent AI-detection suggests the figure is substantially higher. We explore a number of features of the texts, particularly the high occurrence of present participle clauses in their work, which seems to be characteristic of AI-generated texts. Instead of simply focusing on correcting AI-generated texts or the ethical ramifications of using such tools, teachers are invited to reflect on sociolinguistic aspects that should be considered during assessments.